Masculinity as a site of pre-emptive intervention in the prevention of child sexual abuse : a thesis presented in partial fulfilment of the requirements of Doctor of Clinical Psychology at Massey University, Manawatu, New Zealand - Mowat, Keith Philip (Massey University, 2012)
This research aimed to challenge dominant assumptions regarding paedophilia and child sex offending and open up the possibility for interventions that engage men before they offend against children. Child sexual abuse (CSA) remains a serious social problem that is overwhelmingly committed by men, and yet masculinity is usually excluded from Criminal Psychology’s endeavours to understand child sex offenders (CSO). Positivist approaches to the prevention of CSA have excluded dominant gendered power relationships. A poststructuralist informed reading of the literature revealed blurred boundaries between media representations and psychological constructions of CSO, producing a deviant subject that obscured gendered social power relationships and the discourses of hegemonic masculinity (HM) that are implicated in CSA. This thesis questions the pervasiveness and longevity of HM, and its effects, in order to produce a space to examine the narratives of four former CSO. The first analysis chapter used narrative theory to form a hybrid representation of the men’s stories. This revealed a dominant form of normative heterosexuality where masculine privilege was so embedded in cultural practices that it was rendered invisible. It also located turning points in the men’s negotiations of masculinity that led to their offending. The second analysis chapter involved a discourse analysis of the discursive constitution of masculinity in the men’s talk. Together these chapters offer potential points of pre-emptive intervention and the potential for institutions to address cultural assumptions of heteronormativity.
Keywords: Child abuse prevention; Masculinity; Hegemonic masculinity